2012
DOI: 10.1186/1475-925x-11-31
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of three surgical scenarios of posterior lumbar interbody fusion by finite element analysis

Abstract: BackgroundFor the treatment of low back pain, the following three scenarios of posterior lumbar interbody fusion (PLIF) were usually used, i.e., PLIF procedure with autogenous iliac bone (PAIB model), PLIF with cages made of PEEK (PCP model) or titanium (Ti) (PCT model) materiel. But the benefits or adverse effects among the three surgical scenarios were still not fully understood.MethodFinite element analysis (FEA), as an efficient tool for the analysis of lumbar diseases, was used to establish a three-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 31 publications
9
35
0
Order By: Relevance
“…Our results suggest that the patients who underwent posterior lumbar interbody fusion surgery with total laminectomy operation are likely to experience a higher incidence of ASD than those who underwent posterior lumbar interbody fusion with hemi-laminectomy operations, which were in accordance with the previous clinical studies [3, 11]. Biomechanically, the SSL and ISL act as a tension band in an intact spine, especially during flexion [23, 24]. In the PLIF-LAM model, the removal of the whole L4 spinous process would damage the SSL, ISL or the anchoring point of the neighboring unfused segments, jeopardize the effect of the tension band, and thus causing the accelerated development of ASD.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results suggest that the patients who underwent posterior lumbar interbody fusion surgery with total laminectomy operation are likely to experience a higher incidence of ASD than those who underwent posterior lumbar interbody fusion with hemi-laminectomy operations, which were in accordance with the previous clinical studies [3, 11]. Biomechanically, the SSL and ISL act as a tension band in an intact spine, especially during flexion [23, 24]. In the PLIF-LAM model, the removal of the whole L4 spinous process would damage the SSL, ISL or the anchoring point of the neighboring unfused segments, jeopardize the effect of the tension band, and thus causing the accelerated development of ASD.…”
Section: Discussionsupporting
confidence: 87%
“…Oppositely, the removal of the posterior complex eliminated the tension band effect in the flexion motion [4, 7], which may thus produce larger forces on the PLL, ITL and CL to resist to flexion loading. Several authors reported that the changes in load sharing among ligaments would alter the normal physiological and mechanical environments of ligaments, leading to ligament failure and hypertrophy [24, 25]. Moreover, the increase in ligaments forces were likely relevant to the invocation of pain and prone to cause chronic soft tissue injury, facet joint degeneration as well as hypertrophy of the LF, and thereby cause the ASD [5, 23, 24, 26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Interaction Property "TIE" in ABAQUS was used to define all the surface to surface contacts in the FE models [35].…”
Section: Boundary and Loading Conditionsmentioning
confidence: 99%
“…Finite element analysis (FEA) is one technique that can be used for in vitro biomechanical and biomaterial studies. FEA is an indispensable biomechanical evaluation tool for supplementing in vitro biomechanical studies of the spine [9][10][11][12][13]. Most previous studies of PLIF using FEA have not taken into account the strength of osteoporotic bone in the elderly, and FEA analysis of PLIF in a model simulating vertebral bodies of normal bone strength for young people found almost no fractures [14], with the damage elements localized at the part of the bone around the cage.…”
Section: Introductionmentioning
confidence: 99%